(REVIEW) Danuta Plecka and Zuzanna Osmólska (eds.), Public Administration. Local elections in 2014, Adam Marszałek Publishing House, Toruń 2015, pp. 300 - Hoppe, Aleksandra (Political Preferences, 2016)
The joint publication edited by Danuta Plecka and Zuzanna Osmólska entitled “Public Administration. Local elections in 2014” is still a current experience in 2016. The reviewed book, that was released last year, is the latest entry in the “Local government in the 21st century” series, which was published by Adam Marszałek Publishing House under the direction of professor Joanna Marszałek-Kawa from Toruń. The thesis edited by Danuta Plecka and Zuzanna Osmólska consists of 21 articles and as editors in the appropriate to the entire book introduction indicate it is the result of successive thoughts and analysis on public administration.